Perbedaan Pemberian Kurma (Phoenix dactylifera) terhadap Kelelahan Kerja pada Pekerja Bagian Finishing di PT. PP (Persero) Tbk. - Sarah Retno Astrini; Ida Wahyuni; Baju Widjasena (Jurnal Kesehatan Masyarakat (Undip), 2015)
Work fatigue is one form of body defense to avoid more severe damage again and puts the mark on the body to rest. Enough rest accompanied by adding calories to replace much-needed energy quickly for the body that did heavy work such as finishing in the construction company. To overcome these problems can be done the addition of calories contained in the date palm (Phoenix dactylifera). The purpose of this research is to analyze the difference in delivery dates (Phoenix dactylifera) against change fatigue work on finishing parts workers at PT PP (Persero), Tbk. This type of research is Quasi Eksperiment and design used in this study is Non-equivalent control group pretest -post test design. The population is 10 people who worked at finishing area. The result showed p < 0.05 (0,893) which meant that there is a difference of change fatigue work with negative value at Z =-0,135 meaning value (control group) is smaller than the value (treatment Group). Analysis result showed no difference between the giving of the date palm (Phoenix dactylifera) to change in work fatigue. The advice of researchers provides additional energy in the form of food-rich interludes natural sugars to workers in order to reduce the degree of fatigue in work.